Health impact of the exposure to fibres with fluoro-edenitic composition on the residents in Biancavilla (Sicily, Italy): mortality and hospitalization from current data - Susanna Conti; Giada Minelli; Valerio Manno; Ivano Iavarone; Pietro Comba; Salvatore Scondotto; Achille Cernigliaro (Istituto Superiore di Sanità, 2014)
INTRODUCTION. The objective of this chapter is to study the health impact of the exposure to fibres with fluoro-edenitic composition on the residents in Biancavilla (Sicily, Italy), in terms of mortality and hospitalization. The diseases which international scientific literature indicates as associated with asbestos exposure were taken into consideration: mesothelioma of pleura, peritoneum, pericardium and tunica vaginalis testis, malignant neoplasm of larynx, malignant neoplasm of trachea, bronchus and lung, malignant neoplasm of ovary, pneumoconiosis; moreover, in order to describe the health profile of the study population, large groups of diseases were taken into consideration. MATERIAL AND METHODS. Current data (available in the Data Bases of the Unit of Statistics of ISS) regarding mortality and hospitalization were analyzed. Standardized Mortality Ratios, Standardized Hospitalization Ratios and Age-standardized Death Rates were calculated. The demographic background of the population residing in Biancavilla was also outlined. Conclusions. Our findings support the etiologic role of fibres with fluoro-edenitic composition in the occurrence of the above mentioned diseases, already observed in other studies.